PENGARUH PENGALAMAN KERJA, KOMPETENSI TERHADAP KINERJA MELALUI PENGEMBANGAN SDM DI BPSDM HUKUM DAN HAM - Sri Endah Nurhidayati, (2021)
This study aims to analyze work experience, competence through HR development on employee performance at BPSDM. The sample of respondents in this study were 73 employees and the sample selection used was through a questionnaire with simple random sampling. Using quantitative methods with data analysis techniques using Structure Equation Models (SEM) using Partial Least Square (PLS). This study shows that work experience has a value of 0.283 in the original sample, which means it has a positive influence on employee performance. Competence with a value of 0.274 which means that competence has a positive influence on employee performance, HR development gets an original sample value of 0.385 which means that HR development has a positive effect on performance.